Development of Camera and Lens Recognition Learning Media Based on Augmented Reality - Sabrina, Elsa; Novaliendry, Dony; Herayono, Andhika; Firdaus, Firdaus (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This study aims to produce learning media for the introduction of cameras and lenses in Photography subjects using Augmented Reality technology that can be run through smartphones with the android platform. The research method adopted a research and development method using the ADDIE development model, which consisted of five stages: analysis, design, development, implementation, and evaluation. In this research, the stages were limited to the development stage. In designing this photography learning media, the application was made using Unity software, Blender and for database management Vuforia. The instrument used in the study was a learning device validation sheet consisting of several validation sheets, namely: syllabus validation sheet, lesson plan validation sheet, validation sheet and teaching materials. The technique used in this research was observation, interviews, and collecting questionnaires used in data analysis both quantitatively and qualitatively. Validation used expert judgment for the quantitative and qualitative aspects of the assessment representing strongly agree, agree, disagree and disagree. The final result of this research is an Android-based photography learning media that uses Augmented Reality technology.